ANALYSIS CRM, KEPUASAN PELANGGAN DAN LOYALITAS PRODUK UKM BERBASIS BAHAN BAKU TERIGU DI JAWA TIMUR - Dzikiryati Yuni Ersi; Hatane Semuel (Institute of Research and Community Outreach - Petra Christian University, 2014)
Customer relationship management (CRM) is part of a marketing strategy to satisfy and maintain customer loyalty. CRM can be a stimulus to customer satisfaction and loyalty, that the right CRM impact on satisfaction and will affect customer loyalty. The study population is the whole wheat flour SME customers in East Java, and a sample of 139 SME owners were selected by convenience sampling technique, and the analysis technique used is model of Structural Equation Modeling (SEM). The research proves that CRM has a positive effect on customer satisfaction and satisfaction has a positive effect on loyalty. CRM does not have a direct influence on customer loyalty.